Housing Adequacy Gap for Minorities and Immigrants in the U.S.: Evidence from the 2009 American Housing Survey - Kusum Mundra; Amarendra Sharma (Institute for the Study of Labor (IZA), 2014)
Home adequacy for different groups in the U.S. has not been adequately studied. Using the data from the national level American Housing Survey for the year 2009and logit model, this paper finds that there is a significant adequacy difference for Blacks and Hispanics when compared to whites in the U.S. However, that is not the case for immigrants relative to the natives. We also find that then naturalization improves housing adequacy among immigrant homeowners, whereas, the female headed households have a significantly higher home adequacy than that of the male headed households. Similar to the homeownership findings, this paper highlights that the public policies should aim to narrow the home adequacy gap between whites and minorities and encourage naturalization to improve adequacy among immigrant homeowners.
Keywords: R2; J15; 330; housing adequacy gap structural adequacy; U.S. residential real estate; immigrants; minorities; American Housing Survey; naturalized